Impact of Chromosomal Aberrations on Infertility: Diagnosis, Management, and Assisted Reproductive Technologies - Jinan M. Abugharsa (African Journal of Advanced Pure and Applied Sciences, 2025)
Chromosomal polymorphisms may be linked to infertility since they are more common among infertile couples However, their exact impact on reproduction, particularly when assisted reproductive technologies (ART) are used, remains unclear. This review article aims to explore infertility related to chromosomal aberrations and discuss the techniques that are used for diagnosis. Most faulty oocytes exhibit numerical abnormalities (monosomy, trisomy), while most abnormal spermatozoa show structural defects (translocations, inversions, deletions, and duplications). These differences in defect types lead to aneuploidy, miscarriages, and infertility. Azoospermia, oligospermia, and gonadal dysgenesis are indicators of spermatogenic failure and characteristic features of male chromosomal infertility. Additionally, factors affecting ovarian development, oocyte maturation, fertilization competence, pre-implantation embryo development, implantation, and fetal support are key contributors to female infertility. Performing a karyotype before beginning any in vitro fertilization (IVF) procedure is advisable, as it helps reduce the risk of procedural failure. The review also emphasizes the importance of understanding specific chromosomal abnormalities in infertile individuals, which can lead to more personalized treatment approaches. Tailoring treatments may potentially improve the success rates of assisted reproductive technologies and reduce the risk of miscarriages and genetic disorders in offspring. This highlights the critical role of genetic counseling and advanced diagnostic techniques in managing infertility and achieving better reproductive outcomes.